Supporting English Learners: Overcoming Anxiety and Building Confidence - Diasamidze, Medea; Samnidze, Nino (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
Learning English is not merely the acquisition of grammar rules and vocabulary; it is a deeply human process influenced by learners’ motivation, emotional states, and self-belief. Many students face challenges such as anxiety, fear of making mistakes, or low confidence, which can hinder their participation and progress. This paper explores how psychological factors-including motivation, self-efficacy, and affective barriers-impact English language learning, and how teachers can apply practical strategies to address these challenges. Drawing on foundational theories from Gardner, Krashen, Vygotsky, Deci & Ryan, and MacIntyre, the study combines a comprehensive literature review, detailed classroom observations, and a case-based analysis of first-year economics students at the A2 English level. The findings illustrate that when teachers create supportive, engaging, and psychologically-informed learning environments, students are more willing to take risks, actively participate, and gradually transform from hesitant learners into confident users of English. Ultimately, the paper demonstrates that attending to the psychological dimensions of learning not only enhances language proficiency but also fosters resilience, self-assurance, and a lifelong enthusiasm for personal and academic growth.